A New Theory in the Appearance of Andalusian Stanzas (A Critical Review of “Andalusian Stanzas and Zajel and Its Impact on Troubadour Poetry” - Sayyed Hussein Mara`ashi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The poetry forms of Stanzas and Zajal and the topics that Andalusian poets address to them are among the issues that are still of interest to the researchers. In this article, we review Mohammad Abbasa's book, which is one of the last studies on this subject. In addition to providing comprehensive information on the Arabic poetry in Andalusia, especially the poetry of Stanzas and Zajal, he presents a new theory in which these two types of poetry are part of the poetry initiatives of the region and its emergence, not influenced by Arabic poetry in the East or European poetry in the West. According to this theory, contrary to the opinion of many scholars, Stanzas and Zajal have been influenced by part of European poetry called Troubadour; conversely, they are not correct. The descriptive content analysis method was used for criticism and reviewing the effect of this topic. According to the review, Mohammad Abbasa's theory is largely acceptable, but still parts of it need more indicia.